Establishing a Digital Participation Bank in North Macedonia: Opportunities and Challenges in Interest-Free Finance - Lokce, Ahmet; Bojadzievska Danevska, Andrijana (Naše gospodarstvo/Our economy, 2025)
This paper aims to explore the feasibility of establishing a digital participation bank in North Macedonia based on the principles of interest-free finance. This system has been part of ethical and equitable financial systems in the major Abrahamic religions. Thus, as interest-free finance becomes more popular worldwide, digital banking presents a new approach to incorporating these principles into the Macedonian banking system. Here, the purpose of the paper is to discuss the applicability of establishing a digital participation bank in North Macedonia based on interest-free finance principles, by drawing on global best practices. In that sense, this paper provides an analysis of the interest–free finance and intends to describe the banking environment in North Macedonia and the necessary regulatory and market changes. Furthermore, it offers recommendations for integrating ethical, interest-free finance into the Macedonian digital banking sector. Findings indicate that the country has strong potential, due to its diverse population, growing SMEs sector and demand for ethical financial services, but at the core, significant legal and institutional changes are required. Finally, the paper concludes with the opportunities that digital interest-free finance has in financial inclusion, investment attractiveness, and integration with the digital transformation strategy; while detected challenges refer to regulatory changes, consumer and institutional education.
Keywords: Digital participation banking; Interest-free finance; Ethical finance; Digital transformation